SISTEM INFORMASI PENCATATAN SERVICE KENDARAAN TOYOTA BERBASIS WEB - Satria Satria (KILAT, 2018)
Astrido Jaya Mobilindo is one of Toyota's authorized dealers engaged in the automotive field which includes the sale of goods and services. Almost all existing systems are computer based. However, in its implementation there are still deficiencies in helping employees such as the absence of a report system in the form of graphs to facilitate the head of the workshop in analyzing the performance of the workshop and the inequality of work provided by each technician because the foreman cannot monitor the work of each technician. Therefore, the improvement of services in work must continue to be improved. The author makes a web-based vehicle service recording system with the waterfall method, where this method helps in the system development stages that are running there. Toyota's web-based service registration system has the advantage that the distribution of work to technicians is more faired and equitable with a monitoring display and can more quickly display service productivity reports because direct reports are displayed in graphical form and produce more accurate information with the smallest possible risk of error and more effective and efficient in data manipulation.